1994
DOI: 10.1007/bf03347731
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth hormone insulin like growth factor-I axis in Down’s syndrome

Abstract: As GH therapy has been reported to increase growth velocity in children with Down's syndrome (DS), we studied the GH-IGF-I axis in some DS patients affected by growth retardation without serious congenital malformation, malnutrition or pathological thyroid or adrenal function. IGF-I and IGF-II were evaluated in 39 patients in basal conditions. The patients were subsequently divided into two groups with respect to the IGF-I basal value: Group 1 (GR 1) consisting of patients with abnormally low basal IGF-I conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…It acts through IR/IGF-IR, IRS, and RAS/MAPK or PI3K/AKT in regulating neurogenic cell fate [125]. Decreased levels of IGF-I have been found to associate with growth retardation in DS patients, which could be rescued by GH therapy [126,127]. In addition, the insulin receptor knockout mouse suggests that neurons without insulin receptor exhibit significant reduction of Akt and Gsk3beta and increased tau hyperphosphorylation, characteristics of neurotoxicity in DS and AD [128].…”
Section: Insulin Signalingmentioning
confidence: 99%
“…It acts through IR/IGF-IR, IRS, and RAS/MAPK or PI3K/AKT in regulating neurogenic cell fate [125]. Decreased levels of IGF-I have been found to associate with growth retardation in DS patients, which could be rescued by GH therapy [126,127]. In addition, the insulin receptor knockout mouse suggests that neurons without insulin receptor exhibit significant reduction of Akt and Gsk3beta and increased tau hyperphosphorylation, characteristics of neurotoxicity in DS and AD [128].…”
Section: Insulin Signalingmentioning
confidence: 99%
“…On the basis of these data, it is conceivable that any end-organ resistance in DS is partial, rather than complete. We should emphasize that severe short stature, common to both subgroups of DS in our study (Table 1), is a cardinal characteristic of DS and is not associated with GH deficiency (27,28) or any other endocrinopathy.…”
Section: Discussionmentioning
confidence: 55%
“…Some authors reported reduction of IGF-I levels in DS patients, without any age-related differences, to an extent similar to that in GHD patients [165,[170][171][172], while others showed a progressive decrease during advacing age, although within the age-related normal range [173]. Nutritional, lifestyle and/or social differences may explain these controversial findings.…”
Section: Gh/igf-i Axis In Down's Syndrome: a Clin-ical Model Of Anticmentioning
confidence: 97%
“…Nutritional, lifestyle and/or social differences may explain these controversial findings. Both hepatic and cerebral IGF-I receptors seem preserved in DS that, in fact, show normal IGF-I sensivity to exogenous GH administration as well as normal GH binding proteins [163,170,172].…”
Section: Gh/igf-i Axis In Down's Syndrome: a Clin-ical Model Of Anticmentioning
confidence: 97%
See 1 more Smart Citation